Digitalization and the Writing Classroom: A Reflection on Classroom Practices - Bickford, Crystal (Journal of Academic Writing, 2020)
This paper outlines the educational benefits of creating digital stories for a variety of academic purposes as well as the professional need for students to develop and showcase digital proficiency. Digital stories fall under the category of multimodal composition and new media studies, and they encourage students to expand their digital literacy skills while reconceptualizing ways in which traditional writing projects can appeal to a broader audience. The article also addresses some of the classroom challenges teachers may face when trying to implement the practice and some practical resources that might assist teachers to integrate digital stories into their classrooms.